Increasing Strategies Sales MSMES Product of XBAG Malang Digitally Through E-Commerce - Dharma, Buyung Adi; Sudarmiatin, Sudarmiatin (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to understand the digital marketing strategies used by the e-commerce project